Industrial heritage re-tooled : the TICCIH guide to industrial heritage conservation - International Committee for the Conservation of the Industrial Heritage; Douet, James (Lancaster : Carnegie publishing, 2012)
This volume comprises the authoritative work from the International Committee for the Conservation of the Industrial Heritage - the international group dedicated to industrial archaeology and heritage - detailing the latest approaches to the conservation of the global industrial heritage. With contributions from over thirty specialists in archaeology and industrial heritage, Industrial Heritage Re-tooled establishes the first set of comprehensive best practices for the management, conservation, and interpretation of historical industrial sites. This book:-defines the meaning and scope of indus.
29. Teaching in Schools -- Gràcia Dorel-Ferré30. University Training -- Györgyi Németh; 31. Distance and On-line Learning -- Tuija Mikkonen; Part VI: TICCIH; 32. The Work of TICCIH -- Stuart B Smith; 33. TICCIH's Charter for Industrial Heritage -- Eusebi Casanelles; Appendix: The Nizhny Tagil Charter for the Industrial Heritage; Index
Includes index.
Description based on online resource; title from PDF title page (ebrary, viewed March 13, 2015).
Keywords: Historic industrial sites; Historic preservation; Historic sites -- Conservation and restoration; Historic sites -- Conservation and restoration; Industrial archaeology; Industrial sites -- Conservation and restoration; Industrial sites